2017
DOI: 10.3389/fmicb.2017.01986
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retrovirus-K and TDP-43 Expression Bridges ALS and HIV Neuropathology

Abstract: Despite the repetitive association of endogenous retroviruses in human disease, the mechanisms behind their pathological contributions remain to be resolved. Here we discuss how neuronal human endogenous retrovirus-K (HERV-K) expression in human immunodeficiency virus (HIV)-infected individuals is a distinct pathological aspect of HIV-associated neurological conditions, such as HIV encephalitis and HIV-associated neurocognitive disorders. Enhanced neuronal HERV-K levels were observed in the majority of HIV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 81 publications
(108 reference statements)
1
37
0
Order By: Relevance
“…TDP-43 protein aggregation has emerged as a unifying pathological marker of a majority of ALS and frontotemporal lobar degeneration (FTLD) cases [ 44 ]. Correlation of TDP-43 and HERV-K(HML-2) RT and pol expression in brain tissues has been reported [ 42 , 45 ], although that link is controversial. Although Li et al [ 46 ] reported TDP-43 protein bound the HERV-K LTR with an attendant increase in HERV-K transcription and RT activity, Manghera et al [ 47 ] found that wild-type TDP-43 binds the HML-2 LTR without altering transcription, while mutant TDP-43 promotes HML-2 RT protein aggregation resulting in its clearance from astrocytes but not neurons.…”
Section: Introductionmentioning
confidence: 99%
“…TDP-43 protein aggregation has emerged as a unifying pathological marker of a majority of ALS and frontotemporal lobar degeneration (FTLD) cases [ 44 ]. Correlation of TDP-43 and HERV-K(HML-2) RT and pol expression in brain tissues has been reported [ 42 , 45 ], although that link is controversial. Although Li et al [ 46 ] reported TDP-43 protein bound the HERV-K LTR with an attendant increase in HERV-K transcription and RT activity, Manghera et al [ 47 ] found that wild-type TDP-43 binds the HML-2 LTR without altering transcription, while mutant TDP-43 promotes HML-2 RT protein aggregation resulting in its clearance from astrocytes but not neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The immune-mediated retrotranscription of specific HERVs was shown possibly to negatively influence the outcome of CNS disorders (Douville et al, 2011;Douville and Nath, 2017;Kremer et al, 2013;Küry et al, 2018). While our work unravels the putative evolutionary-determined advantage conferred by the immune/MER41/cognition pathway in human, it also points to the potential weaknesses that are inherent to such a pathway.…”
Section: Accordinglymentioning
confidence: 74%
“…Based on experiments in cultured human cells, Drosophila (fruit fly) and mice TDP-43 models, it is possible that HERV RT protein levels are being increased by TDP-43 through a not yet clear mechanism (11,(24)(25)(26). Interestingly, HIV infection of the CNS also leads to neuroinflammation, increased TDP-43 expression, and increased HERV expression (27).…”
Section: Mechanismsmentioning
confidence: 99%